Vitamin D deficiency as a risk factor for dementia and Alzheimer’s disease: an updated meta-analysis - Chai, Bingyan; Gao, Fulin; Wu, Ruipeng; Dong, Tong; Gu, Cheng; Lin, Qiaoran; Zhang, Yi (BMC neurology, 2019)
Background We aimed to comprehensively explore the associations between serum 25(OH)D deficiency and risk of dementia and Alzheimer’s disease(AD). Methods We systematically searched Pubmed, the Cochrane Library, Embase and the reference lists of pertinent review articles for relevant articles published from database inception up until January 2019. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated with random effects models using the Stata 12.0 statistical software package. Results Twelve prospective cohort studies and four cross-sectional studies were included in this meta-analysis. The pooled HRs of dementia and AD, respectively, were 1.32 (95%CI: 1.16, 1.52) and 1.34 (95%CI: 1.13, 1.60) for vitamin D deficiency (< 20 ng/ml). In the subgroup analyses, the pooled HRs of dementia and AD, respectively, were 1.48 (95%CI: 1.19, 1.85) and 1.51 (95%CI: 1.04, 2.18) for moderate vitamin D deficiency (10–20 ng/ml) and 1.20 (95%CI: 0.99, 1.44) and 1.36 (95%CI: 1.01, 1.84) for severe vitamin D deficiency (< 10 ng/ml). Conclusion There are significant associations between vitamin D deficiency and both dementia and AD. There are stronger associations between severe vitamin D deficiency (< 10 ng/ml) and both dementia and AD compared to moderate vitamin D deficiency (10–20 ng/ml).